Scrutinizing Potential Phytoconstituents from Bauhinia variegata in Mitigating the Symptoms of Polycystic Ovarian Syndrome: A Computational Approach - Narayanan, Pavithra Lakshmi; Vellapandian, Chitra (Indian Journal of Pharmaceutical Education and Research, 2024)
Background Polycystic ovarian syndrome is a metabolic disorder majorly caused by the hormonal fluctuations in female and the current scenario explains that adolescents remain predominantly affected with this disorder. Bauhinia variegata assist in the treatment of various ailments and are used as an ingredient in targeting uterine disorders, yet the exact constituent that contributes on activity remains unknown. Aim The main aim of our study is to determine the potent phytoconstituent of Bauhinia variegata to fight against the symptoms of PCOS through computational techniques. Materials and Methods Five in silico techniques like Molecular docking analysis, Pharmacokinetics, toxicity prediction of the compounds, Biological activity and Molecular dynamics simulation studies were performed to identify the potent phytoconstituent. Results and Discussion Molecular docking studies show that the major constituent lupeol had a good binding interaction and high docking score of -10.31 Kcal/mol and -11.52 Kcal/mol with both the proteins 3RUK and 1E3K. Pharmacokinetics, toxicity and biological activity studies reveal that it had ideal drug likeliness properties with proper biological activity values and were found to non-toxic in the analysed parameters. Lupeol complex was found to be potentially stable throughout the molecular dynamic’s simulation for 100 ns. Conclusion Thus, through in silico analysis it is evident that from the list of phytoconstituents of Bauhinia variegata, lupeol possess potent activities in mitigating the symptoms of PCOS. Further in vitro and in vivo analysis on PCOS model is expected to yield favourable results.
Keywords: Bauhinia variegata; Molecular docking; Molecular dynamics; Pharmacokinetic analysis; Toxicity prediction